HUBUNGAN TINGKAT PENGETAHUAN DAN PRAKTIK PERAWAT MENGENAI KESELAMATAN PASIEN (PATIENT SAFETY) DI INSTALASI GAWAT DARURAT RS X SEMARANG - Vena Jaladara; Siswi Jayanti; Ekawati Ekawati (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2015)
In Indonesia, reports regarding patient safety has not been noticed and concerned decently, but the arraignments toward malpractice are increasing. Nurses, are the spearhead of the health care. Emergency room is one of healthcare area that needs fast and right treatment, so that the nurses should have good knowledge and practice regarding patient safety.The purpose of this study was to determine the correlation between nurses knowledge and nurses practice or the implementation regarding patient safety at emergency room of X Hospital Semarang. This study is belong to an explanatory research with cross sectional approach. The population that used was total sampling, with 35 nurses which are working at emergency room of X Hospital Semarang. Data was collected directly used questionnaire that is based on Joint Commission International (JCI).Chi Square test was used to analyze the data. The results of statistical test showed that there is a correlation between nurses knowledge regarding patient safety with the implementation of patient safety at emergency room of X Hospital Semarang with p value=0,000. Socialization and review concerning patient safety should be given periodically by nurse supervisor.